Recent development in integrated Lithium niobate photonics - Zhenda Xie; Fang Bo; Jintian Lin; Hui Hu; Xinlun Cai; Xiao-Hui Tian; Zhiwei Fang; Jinming Chen; Min Wang; Feng Chen; Ya Cheng; JingJun Xu; et al. (Advances in Physics: X)
The lithium niobate on insulator devices confine the light field to submicron size in monocrystalline lithium niobate, to achieve ultra-strong electro-optical interaction and nonlinear optical interaction, and thus extend the frontiers of the photonic research in the past decade. Such devices are manufactured using nano-fabrication technology over the thin-film lithium niobate wafer, which usually stands on a silica insulator layer above the substrate material, including low-loss waveguides, electro-optical modulators, domain engineered structures, high-Q microring resonators and electrical filters etc., and lead to breakthroughs in optical communication, microwave photonics and quantum integration.